Dorothy Dale's engagement - Penrose, Margaret; Owen, Robert Emmett, 1878-1957 (Salt Lake City, UT : Project Gutenberg, 2023)
"Dorothy Dale's Engagement" by Margaret Penrose is a novel written in the early 20th century. This installment follows the main character, Dorothy Dale, and her adventurous chum Tavia Travers as they navigate life changes and romantic interests during their first trip to New York City without an adult chaperone. The story centers on their experiences as they shop and inadvertently encounter a charming young man named G. Knapp, whose presence stirs feelings and complications in Dorothy's otherwise sensible life. The opening portion of the book introduces Dorothy and Tavia as they travel to New York City, discussing their plans and dealing with the hustle of the city life. Their excitement is met with a mix of humor and chaotic situations, including an encounter with G. Knapp, who assists them with their luggage. The girls$1 (Bcontrasting personalities come to the forefront$1 (BTavia is playful and flirtatious, while Dorothy is more composed and practical. As they navigate the city, Tavia loses her handbag, setting off a chain of events that leads to potential trouble, ultimately introducing elements of mystery and romance in their unexpected encounters with G. Knapp. This sets the stage for adventure and exploration of young love amidst the backdrop of an exciting urban landscape. (This is an automatically generated summary.)s
Release date is 2023-11-05
Bob Taylor, David Edwards and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Friendship -- Juvenile fiction; Young women -- Juvenile fiction; Man-women relationships -- Juvenile fiction